Extension Program Design for Utilizing Oil Palm Fronds to Produce Briquettes in Padang Bolak Julu District, North Padang Lawas Regency - Fachrurrozy Ahmad Ritonga; Firman Raydav Lamtorang Silalahi; Azis Herdiyanto Riyadi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Oil palm plantations generate substantial quantities of underutilized frond waste, creating environmental concerns while limiting opportunities for value-added use. Converting oil palm fronds into briquettes offers a renewable energy solution that can simultaneously improve agricultural waste management and create additional economic opportunities for farmers. This study aims to develop an agricultural extension program, evaluate farmers’ acceptance of its design, and assess its effects on farmers’ knowledge, attitudes, and practical skills related to briquette production from oil palm fronds in Padang Bolak Julu District, North Padang Lawas Regency. Conducted from March to April 2026, the study employed an evaluative approach combining an assessment of the extension program design with an evaluation of its outcomes. Thirty farmers were selected through purposive sampling. Data were collected through observations, questionnaires, documentation, and pretest and posttest assessments and analyzed descriptively using percentage analysis and continuum-scale interpretation. The findings indicate that all extension components, including instructional materials, teaching methods, learning media, program intensity, location, scheduling, and implementation costs, were categorized as highly effective. Farmers’ knowledge increased from 45.13% before the intervention to 84.87% afterward, while their attitudes toward the innovation were highly positive, with a score of 84.27%. Moreover, 76.67% of participants were classified as skilled in briquette production. The economic feasibility analysis produced a revenue–cost ratio of 1.72, indicating that briquette production is financially viable. The study concludes that a participatory and context-based extension program can effectively facilitate behavioral change and promote the conversion of oil palm fronds into value-added products. These findings provide practical implications for the development of locally responsive agricultural extension programs that support sustainable waste management, renewable energy production, and improved economic opportunities for farming communities.